GAMBARAN GAYA KEPEMIMPINAN KEPALA PRODUKSI PT HSL - Tenandidjaja, Stefanus Justian; Ferliana, Jovita Maria (Noetic Psychology, 2011)
One of a competent resource that is needed by a company to survive and develop is leader. Bernard Bass stated that every leader need to have two kinds of leadership style, i.e. transformational and transactional leadership style. Based on the factual complaints that derived from PT HSLÃ¢â¬â¢s employees especially to the leader of production division, this study want to explain the leadership style of that leader. Quantitative-descriptive used in this study. A-120 employees of division production are participated by filling a psychological instrument named Multifactor Leadership Questionnaire (MLQ, ÃÂ± = 0,825). This study found that PT HSLÃ¢â¬â¢s leader of production division was rated under-average either transformational or transactional leadership style (Mtransformational = 50,69<54; Mtransactional = 32,33<33). Further, 42 employees (35%) perceived the PT HSLÃ¢â¬â¢s leader of production division poorly on both leadership styles.ÃÂ Keywords: leadership style, Multifactor Leadership Questionnaire, MLQ